PENCEGAHAN STUNTING MELALUI EDUKASI ISI PIRINGKU UNTUK MENINGKATKAN PERAN IBU DALAM KELUARGA - Hasanah, Tita; Awaludin S., Muhamad Robie; Humairoh, Aninda Nishfi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
Mothers have an important role in the family to prevent stunting in their children. However, not all mothers have the knowledge to carry out this function. This community service activity aims to provide education to mothers to prevent stunting through the Isi Piringku education. The approach method for this activity is service learning which is carried out in Ciampea Udik Village, Bogor Regency. The activity was attended by 19 mothers who have elementary school-aged children. The stages of the activity consist of planning, implementation, and evaluation. The material provided is about Introduction to Isi Piringku and Childcare. The characteristics of the education participants are mostly in early adulthood with a secondary education level which shows that the type of participants is right on target. The response of all participants to this activity was that it was useful and interesting, and more than half of them hoped that educational activities would be carried out routinely. The implication of this activity is that further activities are needed in the form of education for students and media development about Isi Piringku for children and families.